(untitled) (Altre Modernità, 2019)
Among the projects for the recovery and reuse of large abandoned industrial areas in Milan - Italy, it is possible to highlight new outcomes that, considering the way in which the redevelopment takes place, both from the perspective of planning, location and relation with the city, create a regeneration process of the industrial historic heritage that produces a completely brand new outcome. An example is that of the two projects “City Life-Portello” and “Porta Nuova”, in which the regeneration of derelict areas, within the urban structure, took place with highly intrusive methods and by creating contrapositions between new architectural elements and some historic buildings. In these areas the abandoned space was completely recycled, reinvented and adapted to new uses allowing for creative experiments and launching completely new design experiences for the city of Milan. This happened through the use of “landmarks” of great connotative and semantic force that led these places to become “something else” in the city. At the same time, however, in both cases, the link between past and future is too weak to create a real regeneration process of the industrial historic heritage and the end result is something completely new, "something else" within the city of Milan, from which it differs in shapes, colours, heights and meanings.